دراسة حقلية لتأثير النفط المتسرب في بعض العوامل البيئية وتقديرها في المياه - جاسم محمد الامارة, فارس; مهدي ناصر, علي (University of Thi-Qar Journal of Science, 2010)
A study has been conducted for spilled crude oil in sand reservoir 2x2x1m3 each contains 1200 l water from Garmat Ali River, crude oil was poured in each reservoir as follows: 1.2, 2.4 and 3.6 l in the first three reservoirs respectively while the fourth was  left without oil as control. The four reservoir were exposed to climate under the sun and wind, the changes in the spilled oil layers were investigated as well as some environmental parameters for water underneath which are temperature, salinity and dissolved oxygen. Moreover, petroleum hydrocarbons were measured after certain intervals of 7, 12, 22 and 60 days of exposure. Spilled oil layers reduced with time aspetroleum hydrocarbons dissolved in the water for reservoir with oil in whichconcentrations of dissolved petroleum hydrocarbons increased directly with thickness of oil spill compared with control reservoir. After a week of exposure dissolved petroleum hydrocarbons measured were 833.96 , 1564.33 and 2031.48 μg/l in the reservoir 1,2 and 3 respectively compared with 53.04 μg/l in the control reservoir. These levels were decreased with time in which they reached to 355.22, 623.65 and 1549.21 μg/l in the reservoirs 2 , 3 and 4 respectively after 60 days of exposure. Results were explained onthe basis of biodegradation, photo-oxidation due to increase temperature and decrease dissolved oxygen accompanied the exposure, in which temperature increased directly while dissolved oxygen decreased with exposure time and thickness of spilled oil.